Transcriptome profiling of the Australian arid-land plant Eremophila serrulata (A.DC.) Druce (Scrophulariaceae) for the identification of monoterpene synthases. (April 2017) - Kracht, Octavia Natascha; Ammann, Ann-Christin; Stockmann, Julia; Wibberg, Daniel; Kalinowski, Jörn; Piotrowski, Markus; Kerr, Russell; Brück, Thomas; Kourist, Robert
Abstract: Plant terpenoids are a large and highly diverse class of metabolites with an important role in the immune defense. They find wide industrial application as active pharmaceutical ingredients, aroma and fragrance compounds. Several Eremophila sp. derived terpenoids have been documented. To elucidate the terpenoid metabolism, the transcriptome of juvenile and mature Eremophila serrulata (A.DC.) Druce (Scrophulariaceae) leaves was sequenced and a transcript library was generated. We report on the first transcriptomic dataset of an Eremophila plant. IlluminaMiSeq sequencing (2 × 300 bp) revealed 7, 093, 266 paired reads, which could be assembled to 34, 505 isogroups. To enable detection of terpene biosynthetic genes, leaves were separately treated with methyl jasmonate, a well-documented inducer of plant secondary metabolites. In total, 21 putative terpene synthase genes were detected in the transcriptome data. Two terpene synthase isoenzymatic genes, termed ES01 and ES02, were successfully expressed in E. coli. The resulting proteins catalyzed the conversion of geranyl pyrophosphate, the universal substrate of monoterpene synthases to myrcene and Z-(b)-ocimene, respectively. The transcriptomic data and the discovery of the first terpene synthases from Eremophila serrulata are the initial step for the understanding of the terpene metabolism in this medicinally important plant genus. Graphical abstract: Highlights: The first transcriptome of an Australian medicinal plant E. serrulata (A.DC) Druce is reported. Two monoterpene synthases from Eremophila were cloned in E.coli and characterized. Reviewing of the transcriptome data was crucial in order to identify isoenzymes. 21 putative terpene synthase genes were detected.